Use MATH-WAY it has all the answer
Answer:
The next 3 steps are
Step 4: ![(x+2)=\pm \sqrt{10}](https://tex.z-dn.net/?f=%28x%2B2%29%3D%5Cpm%20%5Csqrt%7B10%7D)
Step 5:
Step 6: ![x=-2+\sqrt{10}\ or\x=-2-\sqrt{10}](https://tex.z-dn.net/?f=x%3D-2%2B%5Csqrt%7B10%7D%5C%20or%5Cx%3D-2-%5Csqrt%7B10%7D)
Step-by-step explanation:
Given:
Quadratic Equation is
x² + 4x - 6 = 0
To Find:
x = ?
Solution:
Step 1: x2 + 4x = 6
Step 2: x2 + 4x + 4 = 6 + 4
Step 3: (x + 2)2 = 10
Step 4: ![(x+2)=\pm \sqrt{10}](https://tex.z-dn.net/?f=%28x%2B2%29%3D%5Cpm%20%5Csqrt%7B10%7D)
Step 5:
Step 6: ![x=-2+\sqrt{10}\ or\x=-2-\sqrt{10}](https://tex.z-dn.net/?f=x%3D-2%2B%5Csqrt%7B10%7D%5C%20or%5Cx%3D-2-%5Csqrt%7B10%7D)
Answer:
y = 1
Step-by-step explanation:
Given that y varies inversely with x then the equation relating them is
y =
← k is the constant of variation
To find k use the condition y = 25 when x =
, then
25 =
= 5k ( divide both sides by 5 )
5 = k
y =
← equation of variation
When x = 5, then
y =
= 1